TIME-DEPENDENT ELASTOPLASTIC CONSTITUTIVE EQUATION OF SOILS AND ITS APPLICATION TO FEM IMPLEMENTATION - T. Okayasu; K. Hashiguchi (International Association of Lowland Technology, 2001)
The time-dependent subloading surface model (Hashiguchi and Okayasu 2000) would predict time-dependent elastoplastic deformation of materials pertinently. In this article the equation of the creep stretching formulated in the previous article for soils is extended so as to predict the time-dependent deformation of soils more accurately. Its adequacy is evaluated by comparisons with test data under undrained triaxial compression. Further, the finite element method (FEM) program for the prediction of time-dependent elastoplastic deformation behavior of soil structures is developed based on the time-dependent subloading surface model, the soil-water coupled formulation and the finite deformation theory. The ability of the FEM program is examined for the simulation of one-dimensional consolidation phenomenon.